2017
DOI: 10.18632/oncotarget.20667
|View full text |Cite
|
Sign up to set email alerts
|

Red and processed meat consumption and colorectal cancer risk: a systematic review and meta-analysis

Abstract: The associations between red and processed meat consumption and the risk of colorectal cancer types have not been conclusively defined. We performed a systematic review and meta-analysis to analyze these associations. We searched PubMed and EMBASE to identify studies published from inception through September 2016. Dose-response, subgroup and subtype analyses of colorectal cancer (colon cancer, proximal colon cancer, distal colon cancer and rectal cancer) were performed. We ultimately selected 60 eligible stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
51
3
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 110 publications
(65 citation statements)
references
References 21 publications
9
51
3
2
Order By: Relevance
“…No association between intake of red meat and risk for rectal cancer was observed. These findings are in line with a recent meta‐analysis published in 2017, in which a positive association between red and processed meat intake and the risk of overall CRC risk, has been reported, but not with rectal cancer risk …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…No association between intake of red meat and risk for rectal cancer was observed. These findings are in line with a recent meta‐analysis published in 2017, in which a positive association between red and processed meat intake and the risk of overall CRC risk, has been reported, but not with rectal cancer risk …”
Section: Discussionsupporting
confidence: 92%
“…With regard to red meat consumption, the results of our study are aligned with several previous epidemiological studies showing a significant association between red meat and CRC risk and have been confirmed by the IARC and WCRF…”
Section: Discussionsupporting
confidence: 91%
“…We found an increased risk of CRC or colon cancer with the frequent intake (almost every day) of processed red meat and risk in women but not in men. Accumulating evidence from meta‐analyses consistently reported an increased risk of CRC with higher intake of processed red meat, although these studies did not present the association by sex. Our findings were also compatible with a recent meta‐analysis of 2 large cohorts (the Nurses’ Health Study and Health Professional Follow‐Up Study), which reported an increased risk of CRC associated with higher intake of processed red meat (>5 vs ≤1 serving/wk) .…”
Section: Discussionmentioning
confidence: 91%
“…In contrast, a recent prospective study in the Swedish population reported that pork intake was associated with an increased risk of colon cancer, whereas beef intake was associated with a decreased risk of colon cancer . Additionally, few studies examined meat‐CRC risk association by subsites of the colon …”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation